Memahami Pluralisme - Kuncoro Condro (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
The idea of ​​pluralism is developing of religious thought, arises by influenced of development of cultural thought, ideology, certain interests, and the power interest. Also the situation of new religions, enter and meet the old religion. At the first, religion is generally exclusivist, but tolerance interest develop it to be inclusive, and finally pluralist, so does for Christianity, as well as other religions. There is truth in each religion, itsmust be respected, but righteous and savetyjust only in its own religion and belief. The real pluralism rejects the notion of every religion can bring its followers to heaven or to save.